Usnic acid, a secondary metabolite of lichens and its effect on in vitro digestibility in reindeer - Palo, R. Thomas (Rangifer, 1993)
Usnic acid, a common secondary metabolite in prefered lichens by reindeer and caribou, has been tested for its effect on In Vitro Dry Matter Digestibility (IVDMD) using inocula from four reindeer. When Cladonia alpestris (stellaris (OpicJ) was used as substrate and reindeer rumen liqour as media of incubation together with usnic acid, digestibility was considerably enhanced. This was also true for a lower prefered lichen Stereocaulon paschale (L.), but the effect was less pronounced. The results suggest that reindeer host some rumen microorganism able to metabolize lichen secondary metabolities.